Masculinities: limits, scope and colonial routes - Ziderich do Amaral, Fernando (Revista Punto Género, 2025)
The objective of this article is to provoke a denaturalization/deconstruction of the concept of masculinity itself, highlighting its colonial, hegemonic and ideological character. We therefore reflect on the rhetorical question: what is masculinity? From this, we begin the work of naming the colonial gender technologies that permeate the field of masculinities, as we expose a project of annihilation of male pluriperspectives. With this, we seek to emphasize the importance of masculinity studies moving alongside the pluriperspectives of existence, paving the way for the flourishing of plurimasculinities as an alternative in breaking with the hegemonic and colonial ideological perspective inserted in the field of masculinities. We seek, therefore, to highlight the violence institutionalized by colonization through the monoculture of masculinity, characterizing its functioning as a colonial gender technology. By showing that Brazilian society operates from a masculinist perspective, we are also making clear that the ideological power relations that take place in this society are based on the colonial gender.